The role of the Central American Journal of Geology in the diffusion of volcanology between 1984 and 2014 - Alvarado, Guillermo E. (2014)
Since 1984, 50 issues of the Revista Geológica de América Central (RGAC) have been published, including a special  unnumbered volume, with the 50th issue published in 2014. The most common topics addressed among all articles include volcanic stratigraphy, petrology, geomorphology and volcanic monitoring. Volcanology-related themes represent 22% of all papers published in RGAC; over 30 years, there have been 86 such papers published, at a rate of 2.8 papers per year. Topics of volcanology are surpassed only by stratigraphy in general, which includes volcanic stratigraphy, radiochronology, and tephrostratigraphy. Since 1994, topics of volcanology have become increasingly common, as noted by several issues with 40 pages or more on related themes. Of the 51 issues of RGAC in 30 years, three were special volumes on Volcanology (No. 30, 2000; No. 43, 2010; and No. 48, 2013). Most published articles are geographically related to Costa Rica (88%), with very little work from the rest of the countries of Central America and none of Guatemala. While the community is working to encourage volcanological and geological studies in the rest of Central America, a number of constraints, particularly a lack of academic researchers in those countries, makes this a difficult task. The challenge for future generations is to maintain and pursue these goals at a national level